Efektivitas Promosi Terhadap Tingkat Penjualan Produk Kartu Halo Pada PT. Telkomsel Di Makassar - Mattarima Mattarima; Roswiyanti Roswiyanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The aim of this research is to determine the effectiveness of promotions on the level of sales of halo card products at PT. TELKOMSEL Sul-sel Makassar. The sample in this research is total promotional cost data and sales level data. The analytical method used is correlation coefficient, linear regression. This shows that there is a very strong and positive relationship between the amount of promotional costs and the increase in the number of halo card sales. This can be seen below, namely r = 0.99. This is based on if r is equal to 1 or close to 1, the relationship between X and Y is very strong and positive..